Using the singular value decomposition to extract 2D correlation functions from scattering patterns. Issue 5 (23rd August 2019) - Bender, Philipp; Zákutná, Dominika; Disch, Sabrina; Marcano, Lourdes; Alba Venero, Diego; Honecker, Dirk
Abstract : The truncated singular value decomposition is applied to extract the underlying 2D correlation functions from small‐angle scattering patterns. Abstract : The truncated singular value decomposition (TSVD) is applied to extract the underlying 2D correlation functions from small‐angle scattering patterns. The approach is tested by transforming the simulated data of ellipsoidal particles and it is shown that also in the case of anisotropic patterns ( i.e. aligned ellipsoids) the derived correlation functions correspond to the theoretically predicted profiles. Furthermore, the TSVD is used to analyze the small‐angle X‐ray scattering patterns of colloidal dispersions of hematite spindles and magnetotactic bacteria in the presence of magnetic fields, to verify that this approach can be applied to extract model‐free the scattering profiles of anisotropic scatterers from noisy data.